Vítimas de traumas não fatais e relação com drogas de abuso - Silva, Marcelo da (2017)
Drug abuse is a risk factor for accidents/violence and/or trauma, in grievance that generate high social costs. The present study aimed to analyze epidemiological, clinical and toxicological characteristics of victims of trauma associated with drugs of abuse. Retrospective study, quantitative, documentary and with toxicological analysis. It was carried out in the municipality of Maringá, Paraná, with cases originating from pre-hospital emergency services in the Northwest of Paraná and enrolled in the Intoxication Control Center of the Regional University Hospital of Maringá from January to August 2016 and toxicological research at the Toxicology Laboratory of the State University of Maringá. It was established an intentional sample of seventy one hospitalized individuals with a medical diagnosis of associated trauma or a probable association with the drugs of abuse, indicated by clinical criteria or victim information, and epidemiological notification as sentinel events in a locoregional drug poisoning surveillance and monitoring program. As data sources for the characterization of the cases were used the Epidemiological records of Toxicological Occurrence of Alcoholic Intoxication and/or Other Drugs of Abuse, and the records of attendance of the pre-hospital services. The Glasgow Scale and Revisited Trauma Score - RTS. . Biological samples obtained from the individuals under study were used to carry out toxicological screening (cocaine and cannabis) and for determining ethanol. Document data was compiled into spreadsheet in Microsoft Office Excel 10.0 Software and analyzed using simple descriptive statistics. For the clinical classification, the percentage of responses to the items of the Glasgow and RTS neurological evaluation scales was analyzed, and the respective scores were measured. Screening was performed by the urine immunochromatography method and the quantitative determination of ethanol was based on dry chemistry and the use of microslides. The research project was submitted to the Committee of Ethics in Research Involving Human Beings of the State University of Maringá, opinion 458.185. The majority of participants were male (67 - 94.4%), with a mean age of 41 years, ranging from 16 to 84 years; the occupation referred by ten (14.1%) was construction work and seven (9.8%) were unemployed. In the majority of cases (58 - 81.7%), the occurrence was in the outdoor environment, mainly in traffic accidents (35 - 49.3%). After trauma, for fifty six cases (78.9%) pre-hospital care was requested. Alcoholic beverages were reported by all of them to hospital admission, but five (7%) used it associated to other drugs (cocaine, marijuana and ecstasy). The pattern of use reported by the majority was chronic (47 - 66.2%). The application of the Glasgow Scale indicated nine cases (17.7%) as moderate or severe, and RTS showed three (6.7%) cases considered moderate or severe, with a clinical condition of bone fractures, traumatic brain injury and excoriations, with psychomotor agitation/aggressiveness and one death. The quantitative determination of ethanol in fifty seven cases indicated that all of them had alcoholic beverages intake - <10mg/dL ethanol in urine in forty eight cases (84.2%) and 10mg/dL to 230mg/dL in nine (15.8%); and nine had used marijuana (15.8%) and five, cocaine (8.8%) associated with alcohol. It was concluded that, in the sentinel event group, alcohol was the drug of abuse associated with violent occurrences, with demand for pre-hospital public attention, to hospitalization and the clinical severity of trauma and death.